Cadmium and lead in cocoa powder and chocolate products in the US Market. Issue 2 (3rd April 2018) - Abt, Eileen; Fong Sam, Jennifer; Gray, Patrick; Robin, Lauren Posnick
ABSTRACT: Cocoa powder and chocolate products are known to sometimes contain cadmium (Cd) and lead (Pb) from environmental origins. A convenience sample of cocoa powder, dark chocolate, milk chocolate, and cocoa nib products was purchased at retail in the US and analysed using inductively coupled plasma mass spectrometry to assess Cd and Pb concentrations. Cd and Pb were evaluated in relation to the percent cocoa solids and to the reported origin of the cocoa powder and chocolate products. Cd ranged from 0.004 to 3.15 mg/kg and Pb ranged from <LOD to 0.38 mg/kg. Cd and Pb were significantly correlated with percent cocoa, with correlations varying by product type and geographic origin. Geographic variation was observed for Cd, with higher Cd concentrations found in products reported as originating from Latin America than from Africa. The influence of percent cocoa solids and cocoa origin on Cd levels are relevant to international standards for Cd in chocolate products.